Relationships Between Alexithymia and Psychopathy in Heroin Dependent Individuals - Psederska, Elena; Savov, Svetoslav; Atanassov, Nikola; Vassileva, Jasmin (Frontiers in Psychology, 2019)
Background: Psychopathy and substance use disorders are highly co-morbid and their co-occurrence is associated with higher severity of addictive behavior and increased risk of violent offending. Both substance use disorders and psychopathy are related to prominent impairments in emotion processing, which are also central features of alexithymia. The nature of the relationship between psychopathy and alexithymia is not well understood and has been particularly understudied among substance dependent individuals. Aims: Our goal was to evaluate the levels of psychopathy and alexithymia in a relatively homogeneous sample of heroin dependent individuals and healthy controls and to examine group differences in the pattern of associations between these constructs. Methods: We examined 62 participants (31 heroin dependent individuals and 31 healthy controls) with the Psychopathy Checklist: Screening version (PCL:SV, Hart et al., 1995) and the Toronto Alexithymia Scale-20 (TAS-20, Bagby et al., 1994). Results: Heroin dependent individuals were characterized by higher levels of both psychopathy and alexithymia as compared to the control group. In addition, heroin dependent individuals with higher levels of psychopathy reported more difficulties in identifying and verbalizing emotional states. In the heroin group, alexithymia was more strongly associated with the impulsive/antisocial characteristics (impulsivity, irresponsibility, antisocial behavior) than with the interpersonal/affective features of psychopathy (grandiosity, manipulativeness, lack of empathy and remorse). Conclusions: Our findings suggest that alexithymia may be one potential mechanism linking psychopathy with opioid use disorders. The development of interventions targeting alexithymia could have significant applications in relapse prevention programs and psychotherapy of substance use disorders with concurrent psychopathy.